Experimental assessment of an End Notched Flexure test configuration with an inserted roller for analyzing mixed-mode I/II fracture toughness. (September 2016) - Boyano, A.; De Gracia, J.; Arrese, A.; Mujika, F.
Highlights: An alternative test configuration to analyze mixed mode I/II fracture. Crack length determination without optical measurements. Determination of GIc and GIIc from a mixed mode test after checking the suitability of the linear criterion. Abstract: This study describes the experimental work related to a test configuration proposed recently, based on an End Notched Flexure test configuration modified with an inserted roller. Various mixed-mode ratio tests have been performed by the variation of the radius or the position of the inserted roller. The crack length during propagation is determined without any optical measurement, based on the experimental compliance of the specimen. Consequently, energy release rate curves have been obtained at each point during the test. As the mixed mode varies during the test, the linear fracture criterion has been used for fitting experimental data of different specimens at different test conditions. The values of G Ic and G IIc obtained after that data fitting agreed with those obtained from pure mode tests.